Development of a core outcome set for cutaneous squamous cell carcinoma trials: identification of core domains and outcomes. (1st June 2021) - Reynolds, K.A.; Schlessinger, D.I.; Yanes, A.F.; Godinez‐Puig, V.; Chen, B.R.; Kurta, A.O.; Cotseones, J.K.; Chiren, S.G.; Iyengar, S.; Ibrahim, S.A.; Kang, B.Y.; Worley, B.; et al.
Summary: Background: The lack of uniformity in the outcomes reported in clinical studies of the treatment of cutaneous squamous cell carcinoma (cSCC) complicates efforts to compare treatment effectiveness across trials. Objectives: To develop a core outcome set (COS), a minimum set of agreed‐upon outcomes to be measured in all clinical trials of a given disease or outcome, for the treatment of cSCC. Methods: One hundred and nine outcomes were identified via a systematic literature review and interviews with 28 stakeholders. After consolidation of this long list, 55 candidate outcomes were rated by 19 physician and 10 patient stakeholders, in two rounds of Delphi exercises. Outcomes scored 'critically important' (score of 7, 8 or 9) by ≥ 70% of patients and ≥ 70% of physicians were provisionally included. At the consensus meeting, after discussion and voting of 44 international experts and patients, the provisional list was reduced to a final core set, for which consensus was achieved among all meeting participants. Results: A core set of seven outcomes was finalized at the consensus meeting: (i) serious or persistent adverse events, (ii) patient‐reported quality of life, (iii) complete response, (iv) partial response, (v) recurrence‐free survival, (vi) progression‐free survival and (vii) disease‐specific survival. Conclusions: In order to increase the comparability of results across trials and to reduce selective reporting bias, cSCC researchers should consider reporting these core outcomes. Further work needs to be performed to identify the measures that should be reported for each of these outcomes.